Molecular and Clinical Significance of Stanniocalcin-1 Expression in Breast Cancer Through Promotion of Homologous Recombination-Mediated DNA Damage Repair - Hou, Jing; Cheng, Jigan; Dai, ZeHua; Wei, Na; Chen, Huan; Wang, Shu; Dai, Min; Li, Leilei; Wang, Hua; Ni, Qing (Frontiers in Cell and Developmental Biology, 2021)
Stanniocalcin 1 (STC1) is a glycoprotein hormone whose abnormal expression has been reported to be associated with a variety of tumors, but its function in breast cancer is not well understood. Through modulation of STC1 expression in different breast cancer cell lines, our study found that STC1 could promote the proliferation and growth of breast cancer cells and promote metastasis. Furthermore, STC1 reduced apoptosis induction by irradiation. We also found that STC1 could promote homologous recombination-mediated DNA damage repair by recruiting BRCA1 to sites of damage. Moreover, STC1 silencing sensitized breast cancer cells to treatment with Irradiation (IR), olaparib or cisplatin in vitro. In clinical settings, the serum concentration of STC1 was higher in breast cancer patients than in healthy women, as detected by ELISA. In addition, immunohistochemical staining of breast cancer specimens showed that high expression of STC1 was negatively correlated with recurrence-free survival in breast cancer, indicating that STC1 expression could be used as a predictive marker for a poor prognosis in breast cancer. All these findings indicate that STC1 promotes breast cancer tumorigenesis and that breast cancers with a high level of STC1 are more resistant to treatment, probably through HR promotion. Furthermore, combining STC1 inhibition and DNA damage-inducing drugs may be a novel approach to improve the survival of patients with STC1-expressing breast cancer.